THE ROLE OF BLOCKCHAIN TECHNOLOGY IN FOOD SECURITY ASSURANCE IN SWEDEN - Nayla Phanpheng; Soneva Vong; Manivone Keolavong (Yayasan Adra Karima Hubbi, 2025)
The study discusses the role of blockchain technology in ensuring food safety in Sweden, with a focus on improving supply chain traceability and transparency. The research aims to identify the extent to which blockchain can improve food safety as well as overcome adoption constraints across companies of various sizes. A qualitative descriptive approach was used, with data collected through interviews and analysis of case studies from food companies. The results show that blockchain is able to improve operational efficiency and regulatory compliance, especially in large enterprises, while small companies face cost constraints and access to technology. The conclusion of the study confirms that blockchain can be a strategic solution for better food security, with the implication that regulatory support and incentives are needed to expand the adoption of this technology in small and medium-sized enterprises.